Reversing the Slide : A Strategic Guide to Turnarounds and Corporate Renewal - Shein, James B., 1942- (San Francisco Jossey-Bass, 2011)
A just-in-time guide for revamping distressed companies Drawn from the author's decades of experience advising, purchasing, and reviving distressed companies across industries, geographies, and sizes, Reversing the Slide is designed to help executives, managers, and employees revitalize downtrodden companies
Include Notes and Index
Keywords: United States -- Strategic planning -- Working capital